Review of Pseudoaerumnosa Rudzinski (Diptera, Sciaridae), with the description of twenty-four new species - Vilkamaa, Pekka; Halenius, Pentti; Ševčík, Jan (Zootaxa, 2019)
The genus Pseudoaerumnosa Rudzinski, 2006 is redefined. The genus includes the following species which are described, illustrated and keyed: Pseudoaerumnosa acinacea sp. n., P. ampliata sp. n., P. annae sp. n., P. awanensis sp. n., P. banari sp. n., P. clavidactyla sp. n., P. clivicola sp. n., P. collicola sp. n., P. consuota sp. n., P. cryptoloba sp. n., P. curvifalx sp. n., P. eminula sp. n., P. exacuta sp. n., P. filispicata sp. n., P. formosa sp. n., P. fragilis sp. n., P. impensa sp. n., P. inviolata Rudzinski, 2006, P. junciseta sp. n., P. obovata sp. n., P. pilicaudata sp. n., P. quadriquetra sp. n., P. saginata sp. n., P. tenuidens sp. n. and P. tkoci sp. n. Morphological characters and the phylogenetic position of Pseudoaerumnosa are discussed. For some species, the barcode (COI) sequence data were obtained. The genus is currently known from the Oriental (22 species), Malagasy (3 species) and Australasian regions (1 species).